An exploratory study on the use of social companion robot for adults with motor disabilities - Abd Malik, Sofianiza; Aburahmah, Linah; Azuddin, Muna (Springer, 2022)
Assistive technology has been a significant topic in both the research and manufacturing industry for the past decades focusing on improving social interaction, supporting health care, business, education, and daily activities. There are different types of assistive technologies such as wearable devices, mobile applications, automated home appliances, and robots. There is lack of study conducted to investigate the use of robots among disabled users, such as adult users with motor disabilities. The aim of this study is to explore the use of a companion robot called Zenbo in assisting motor disability users in Saudi community. This paper presented a preliminary work on Zenbo’s design evaluation in terms of functionality, acceptability, and effectiveness. The study used a mixed method such as observation (hands-on), interview, and survey questions to evaluate the purpose of the study. The findings showed positive acceptance of Zenbo as a companion robot due to the physical design. However, the interaction of Zenbo to notify the users through user interface and wheel light, and processing voice command were found ineffective and require more improvement.